2022
DOI: 10.4274/tjo.galenos.2021.27985
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Stability and Preferred Retinal Locus in Advanced Age-Related Macular Degeneration

Abstract: Objectives: To evaluate fixation stability and characteristics of the preferred retinal locus (PRL) in patients with advanced age-related macular degeneration (AMD). Materials and Methods: Sixty-three eyes of 63 patients with AMD who presented to the low vision unit were included in this prospective study. Sociodemographic characteristics, eye examination findings, and reading performance results with the Minnesota Low Vision Reading test were evaluated. Microperimetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As a tool for assessing the ability to sustain gaze at a fixed target, fixation stability is associated with the duration of the test and the visual function of the patient [37] . Fixation stability has a strong relationship with reading speed [7] and BCVA [40] in patients with CVL, but does not correlate with reading distance [41] . Fixation stability decreases with age in normal healthy people [42] .…”
Section: Use Of Microperimetry In the Patient With Central Visionmentioning
confidence: 92%
See 2 more Smart Citations
“…As a tool for assessing the ability to sustain gaze at a fixed target, fixation stability is associated with the duration of the test and the visual function of the patient [37] . Fixation stability has a strong relationship with reading speed [7] and BCVA [40] in patients with CVL, but does not correlate with reading distance [41] . Fixation stability decreases with age in normal healthy people [42] .…”
Section: Use Of Microperimetry In the Patient With Central Visionmentioning
confidence: 92%
“…The closer the distance between the fovea and TRL, the greater the maximum reading speed, reading acuity, and critical print size [67] . However, Altınbay and İdil [7] found that the foveal-PRL distance had no influence on fixation stability in patients with AMD. Different TRL training frequencies and locations also influenced the effects of biofeedback training.…”
Section: Preferred Retinal Locus Of the Patient With Central Vision Lossmentioning
confidence: 97%
See 1 more Smart Citation